Burnin' Down the House: The 2007 Recession and the Effect on Arson. Issue 5 (4th May 2018) - Powell, Zachary A.
ABSTRACT: In the economics and housing literature, the narrative of the "arsonist for profit" is popularized, where a would-be offender destroys personal property for financial gain. More of than not, arson is expected to increase during periods of economic decline. Over a 12-year period, data on this crime and other demographic variables were collected for 264 counties to study the impact of the 2007 recession on this firesetting. The analyses herein find no support for the profiting arsonist. Implications for future research in this area are discussed.